Riverscape community genomics: A comparative analytical approach to identify common drivers of spatial structure - Zachery D. Zbinden; Marlis R. Douglas; Tyler K. Chafin; Michael E. Douglas (Molecular Ecology, 2023)
Genetic differentiation among local groups of individuals, that is, genetic β‐diversity, is a key component of population persistence related to connectivity and isolation. However, most genetic investigations of natural populations focus on a single species, overlooking opportunities for multispecies conservation plans to benefit entire communities in an ecosystem. We present an approach to evaluate genetic β‐diversity within and among many species and demonstrate how this riverscape community genomics approach can be applied to identify common drivers of genetic structure. Our study evaluated genetic β‐diversity in 31 co‐distributed native stream fishes sampled from 75 sites across the White River Basin (Ozarks, USA) using SNP genotyping (ddRAD). Despite variance among species in the degree of genetic divergence, general spatial patterns were identified corresponding to river network architecture. Most species ( N = 24) were partitioned into discrete subpopulations ( K = 2–7). We used partial redundancy analysis to compare species‐specific genetic β‐diversity across four models of genetic structure: Isolation by distance (IBD), isolation by barrier (IBB), isolation by stream hierarchy (IBH), and isolation by environment (IBE). A significant proportion of intraspecific genetic variation was explained by IBH ( x̄ = 62%), with the remaining models generally redundant. We found evidence for consistent spatial modularity in that gene flow is higher within rather than between hierarchical units (i.e., catchments, watersheds, basins), supporting the generalization of the stream hierarchy model. We discuss our conclusions regarding conservation and management and identify the 8‐digit hydrologic unit (HUC) as the most relevant spatial scale for managing genetic diversity across riverine networks.

Variability of SCCmec in the Zurich area - M. Ender; S. Burger; A. Sokoli; R. Zbinden; B. Berger-Bächi; R. Heusser; M. M. Senn; N. McCallum (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Kinetics of creatine ingested as a food ingredient - Louise Deldicque; Jacques Décombaz; Hermann Zbinden Foncea; Jacques Vuichoud; Jacques R. Poortmans; Marc Francaux (European Journal of Applied Physiology, 2007)

High frequency of multiple paternity in the largest rookery of Mediterranean loggerhead sea turtles - JUDITH A. ZBINDEN; CARLO R. LARGIADÈR; FABIO LEIPPERT; DIMITRIS MARGARITOULIS; RAPHAËL ARLETTAZ (Molecular Ecology, 2007)
Mating systems are a central component in the evolution of animal life histories and in conservation genetics. The patterns of male reproductive skew and of paternal shares in batches of offspring, for example, affect genetic effective population size. A prominent characteristic of mating systems of sea turtles seem to be a considerable intra‐ and interspecific variability in the degree of polyandry. Because of the difficulty of observing the mating behaviour of sea turtles directly in the open sea, genetic paternity analysis is particularly useful for gaining insights into this aspect of their reproductive behaviour. We investigated patterns of multiple paternity in clutches of loggerhead sea turtles in the largest Mediterranean rookery using four highly variable microsatellite loci. Furthermore, we tested for a relationship between the number of fathers detected in clutches and body size of females. More than one father was detected in the clutches of 14 out of 15 females, with two clutches revealing the contribution of at least five males. In more than half the cases, the contributions of different fathers to a clutch did not depart from equality. The number of detected fathers significantly increased with increasing female body size. This relationship indicates that males may prefer to mate with large, and therefore productive, females. Our results suggest that polyandry is likely to increase effective population size compared to a population in which females would mate with only one male; male reproductive contributions being equal.

Etiologic diagnosis of Capnocytophaga canimorsus meningitis by broad-range PCR - J. Gottwein; R. Zbinden; R. C. Maibach; T. Herren (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Courting virtual rivals increase ejaculate size in sticklebacks ( Gasterosteus aculeatus ) - Marc Zbinden; Dominique Mazzi; Reto Knzler; Carlo R. Largiadr; Theo C. M. Bakker (Behavioral Ecology and Sociobiology, 2003)

Sperm allocation in the three‐spined stickleback - M. Zbinden; C. R. Largiadèr; T. C. M. Bakker (Journal of Fish Biology, 2001)
Male three‐spined stickleback Gasterosteus aculeatus have a fixed amount of sperm during the breeding season because spermatogenesis is inhibited at this time. A method was developed to estimate ejaculate size in situ by removing the sperm from the male's nest. The reliability of the method was tested using known numbers of sperm. In their first mating, males ejaculated 11·64 × 10 6 sperm (median), representing c. 5% of the male's sperm store (median 27·88 × 10 7 sperm). The amount of sperm in the testes was significantly reduced in males that had mated several times (median 8·09 × 10 7 ). Additionally, ejaculate size was smaller in these experienced males (median 8·79 × 10 5 ). Heavier and larger fish invested absolutely and relatively more sperm in a mating than did lighter and smaller fish. Ejaculate size did not correlate with the mass of the egg clutch.

Serological Evidence of Human Granulocytic Ehrlichiosis in Switzerland - N. Pusterla; R. Weber; C. Wolfensberger; G. Schär; R. Zbinden; W. Fierz; J. E. Madigan; J. S. Dumler; H. Lutz (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

IgM to Bartonella henselae in cat-scratch disease and during acute Epstein-Barr virus infection - R. Zbinden; Angelika Ströhle; David Nadal (Medical Microbiology and Immunology, 1998)

Serological evidence of human granulocytic ehrlichiosis in Switzerland - N. Pusterla; R. Weber; C. Wolfensberger; G. Schär; R. Zbinden; W. Fierz; J. E. Madigan; J. S. Dumler; H. Lutz (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Evaluation of commercial slides for detection of immunoglobulin G againstBartonella henselae by indirect immunofluorescence - R. Zbinden; N. Michael; M. Sekulovski; A. Graevenitz; D. Nadal (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Mortality of birds of prey following field application of granular carbofuran: A case study - D. R. Dietrich; P. Schmid; U. Zweifel; Ch. Schlatter; S. Jenni-Eiermann; H. Bachmann; U. Bhler; N. Zbinden (Archives of Environmental Contamination and Toxicology, 1995)

LD50 versus acute toxicity - R. Baß; P. Günzel; D. Henschler; J. König; D. Lorke; D. Neubert; E. Schütz; D. Schuppan; G. Zbinden (Archives of Toxicology, 1982)